A 48‐week telaprevir‐based triple combination therapy improves sustained virological response rate in previous non‐responders to peginterferon and ribavirin with genotype 1b chronic hepatitis C: A multicenter study. Issue 14 (15th April 2014) - Shimada, Noritomo; Tsubota, Akihito; Atsukawa, Masanori; Abe, Hiroshi; Ide, Tatsuya; Takaguchi, Koichi; Chuganji, Yoshimichi; Toyoda, Hidenori; Yoshizawa, Kai; Ika, Makiko; Sato, Yoshiyuki; Kato, Keizo; et al.
<x xml:space="preserve">Abstract</x> Aim The sustained virological response (SVR) rate of non‐responders to peginterferon and ribavirin therapy (PR) is low for 24‐week telaprevir‐based triple combination therapy (T12PR24), compared to that of treatment‐naïve patients or previous‐treatment relapsers. This study investigated which characteristics of non‐responders were associated with a better SVR rate to 48‐week therapy (T12PR48). Methods A total of 103 Japanese non‐responders with genotype 1b chronic hepatitis C received telaprevir‐based therapy. Among them, 81 patients (50 partial and 31 null responders) received T12PR24 and 22 (seven partial and 15 null responders) who agreed to the extended therapy received T12PR48. Results Multivariate logistic regression analysis for SVR identified the interleukin‐28B (IL28B) rs8099917 TT genotype (P = 0.0005, odds ratio [OR] = 10.38), extended rapid virological response (P = 0.0008, OR = 7.02), T12PR48 regimen (P = 0.0016, OR = 9.31) and previous partial responders (P = 0.0022, OR = 5.89). Among partial responders, the SVR rate did not differ significantly between T12PR48 (85.7%) and T12PR24 (70.0%). Among null responders, the SVR rate was significantly higher with T12PR48 than T12PR24 (66.7% vs 22.6%, P = 0.0037). Among patients with the IL28B non‐TT genotype, the SVR rate was significantly higher with T12PR48 than T12PR24 (68.8% vs 37.7%, P = 0.0288). Moreover, among null responders with the non‐TT genotype, the SVR rate was significantly higher with T12PR48 than T12PR24 (66.7% vs 9.1%, P = 0.0009). Conclusion T12PR48 improves the SVR rate in null responders, patients with the non‐TT genotype, and null responders with a non‐TT genotype.